Isolation and Characterization of Yarrowia lipolytica YQ22 from Diesel Samples for Phenol Biodegradation - Baldera-Saavedra, Jayson (2023)
Phenolic compounds have gained international interest due to their carcinogenic, toxic, and bioaccumulative properties, causing adverse effects in both animals and humans. As a result, there is a growing interest in finding alternative and eco-friendly treatment routes for phenol by exploring new microbial cultures with potential adaptation and biodegradation capabilities. In this study, the phenol removal efficiency of Yarrowia lipolytica YQ22 under laboratory conditions was determined. The YQ22 strain was obtained from diesel samples from a fuel station in Trujillo, Peru, isolated through serial dilutions on Sabouraud agar, and identified through its morphological characteristics using microscopy and molecular analysis by polymerase chain reaction of the ribosomal DNA internal transcribed spacer (ITS) and 5.8S regions. In the treatment, the effect of pH (5, 6 and 7) and temperature (25°C, 30°C and 35°C) on phenol removal with 2% (v/v) inoculum of Yarrowia lipolytica from 48-hour growth was evaluated. Phenol concentration was measured by high-performance liquid chromatography. A maximum phenol removal percentage of 61.18 was obtained for YQ22 at 30°C, pH 5 and 120 rpm during 48 hours. These findings demonstrate the ability of Yarrowia lipolytica to remove phenol and suggest its potential use in the field of bioremediation of phenolic compounds and their derivatives.